Saint Vitus' dance - Rubalcaba, Jill. (New York : Clarion Books, 1996)
Fourteen-year-old Melanie must come to terms with her mother's incurable illness and the possibility that she herself may develop the disease.
Keywords: Huntington's disease -- Fiction